Wireless Communication Networks and Internet of Things Select Proceedings of ICNETS2, Volume VI - Zungeru, Adamu Murtala; Subashini, S.; Vetrivelan, P.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book is a collection of papers from international experts presented at International Conference on NextGen Electronic Technologies (ICNETS2-2016). ICNETS2 encompassed six symposia covering all aspects of electronics and communications domains, including relevant nano/micro materials and devices. Presenting recent research on wireless communication networks and Internet of Things, the book will prove useful to researchers, professionals and students working in the core areas of electronics and their applications, especially in signal processing, embedded systems and networking.
From Terrestrial to Underground Wireless Sensor Networks: Design Factors and Transmission Cost -- Optimal Energy Saving Through Joint Deployment of Relay Station and Sleep Mode Activation in 4g Lte-A Network -- Efficient Relaying for Enhanced Network Longevity for E-Health Iot Services in Medical Body Area Networks -- Gradient-Based Localization and Relay Nodes Selection in Delay tolerant Mobile Opportunistic Networks for Emergency -- Modelling and Performance Analysis of Wifi offloading -- Integrity Verification for Shared Data in Group With User Revocation -- Shortest Path Solution to Wireless Sensor Networks Using Edge Based Three Point Steiner Tree Concept -- Energy Efficient Elliptic Curve Cryptography Based Dtls Key Establishment Protocol for Iot Communication -- Monitoring Sensor Nodes With Cooja Simulator -- Analysis on Lte/Wi-Fi Data offloading in Hetnets -- Contention-Based Csi Feedback Mechanisms in Mu-Mimo Wlans: A Survey -- Synchronization Analysis of Quadratic Chaos Based Dsss-ofdma System With An Interceptional Attack -- Mean Availability Parameter-Based Ddos Detection Mechanism for Cloud Computing Environments -- An Effective Dynamic Slot Allocation Scheme for Wireless Body Area Network -- Enhancement of Security and Confidentiality for D2d Communication in Lte-Advanced Network Using Optimized Protocol -- Efficient Data Collection Using Dynamic Mobile Sink in Wireless Sensor Network -- Dependency Analysis of Control Parameter Configuration on Isd and Random Mobility of Ue in Lte-A Network -- Throughput Analysis of Macroue for Varied Transmit Power of Small Cell in Heterogeneous Network -- Mobile Foolproof Billing At Supermarkets -- Energy Efficient-Based Optimizing Cluster Head Selection By Geometric Based Mechanism and Implementation Using Soft Computing Techniques -- Enhancement of Qos Parameters in Cluster Based Wireless Sensor Network Using Co-Operative Mimo -- Ber Performance Analysis of Short Reference Differential Chaos Shift Keying Scheme Using Various Maps Over Different Channel Conditions -- Nr-Dcsk Based Mimo Chaotic Communication System -- Wearable Sensor Based Human Fall Detection Wireless System -- Mathematical Analysis of Adaptive Queue Length Based Traffic Signal Control -- Wireless Data Acquisition and Communication System for Automated Guided Vehicle -- Energy Efficient Clusterong Protocol for Wireless Sensor Networks.
Keywords: Wireless communication systems; Mobile communication systems; Electronic circuits; Telecommunication; Lasers; Wireless and Mobile Communication; Electronic Circuits and Systems; Communications Engineering, Networks; Laser